1997
DOI: 10.2151/jmsj1965.75.4_925
|View full text |Cite
|
Sign up to set email alerts
|

Interannual Variability of the Northern Winter Stratospheric Circulation Related to the QBO and the Solar Cycle

Abstract: A statistical study is made of the interannual variability of the northern winter stratospheric circulation in connection with the equatorial quasi-biennial oscillation (QBO) and the solar cycle, by using the 37-year stratospheric dataset of the Freie Universitat Berlin and the 31-year NMC global data.During the period 196263-197778, analyzed first by Holton and Tan (1980, referred to as HT), the polar-night jet is stronger in the W (westerly) than in the E (easterly), as was mentioned by Holton and Tan (1980)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
82
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(86 citation statements)
references
References 13 publications
4
82
0
Order By: Relevance
“…Kodera et al (2000) have shown that the PJO signal is very prominent in the NH winter when stratospheric major sudden warmings take place. Naito and Hirota (1997) have shown that major warmings occur mainly at QBO easterly/solar minimum or QBO westerly/solar maximum. So, we have also conducted the analysis presented in this paper by including QBO effect to see the cross effect as a trial.…”
Section: Discussion and Remarksmentioning
confidence: 99%
“…Kodera et al (2000) have shown that the PJO signal is very prominent in the NH winter when stratospheric major sudden warmings take place. Naito and Hirota (1997) have shown that major warmings occur mainly at QBO easterly/solar minimum or QBO westerly/solar maximum. So, we have also conducted the analysis presented in this paper by including QBO effect to see the cross effect as a trial.…”
Section: Discussion and Remarksmentioning
confidence: 99%
“…Consistently, cold polar temperatures occur during LW and HE van Loon, 1987, 1992; henceforth LvL), although the latter signal is weaker (Labitzke et al, 2006;henceforth LKB06) and its statistical robustness has been challenged (Camp and Tung, 2007;henceforth CT07). Another way of viewing this result Naito and Hirota, 1997) is that the so-called Holton Tan effect Tan, 1980, 1982), in which polar temperatures are colder during wQBO than eQBO, is only effective when the Sun is less active.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between the interannual variability of the stratospheric circulation in the Northern Hemisphere (NH) and the equatorial QBO has been investigated since the 1980's, and it is known that the polar vortex tends to be stronger in the westerly phase than in the easterly phase of the QBO (e.g., Tan 1980, 1982;Dunkerton and Baldwin 1991), although the opposite aspect is observed in the maximum phase of the solar cycle (e.g., Labitzke and van Loon 1988;Naito and Hirota 1997). It is generally considered that a key point is propagation of the planetary waves which is changed due to the latitudinal shift of ''zero-wind line'' (in which the zonal mean flow vanishes) by the QBO.…”
Section: Introductionmentioning
confidence: 99%